(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
It should be noted that the process of learning a language is deeply connected to cultural exposure. Exactly, literature and films play a crucial role in this procedure by providing authentic language input and a rich cultural context. I want to give some information about the role of native cultural materials in language acquisition, focusing on how literature and films enhance linguistic proficiency, cultural awareness, and contextual understanding.It explores applicable theories supporting this approach and suggests practical methods for integrating these materials into language education.